Comparison of Management Practices in Public and Private Universities in Khyber Pakhtunkhwa (Journal of Education and Educational Development, 2020)
This study attempted to compare the management practices in public and private universities in Khyber Pakhtunkhawa, Pakistan. The comparison is based on availability of written rules and regulations, distribution of tasks, availability of managers, access to officers, time management, work load, staff promotion procedure and appraisal system. Additionally, the comparison is also based on transparency, political intervention, use of authorities, nepotism and biasness, human resource availability and functions, academic decisions, existence of different decision making bodies, committees and their role in policy making and implementation and management styles. The population comprised all recognized universities in Khyber Pakhtunkhawa and a convenience sampling of six universities included three from public and three from private sector. The findings showed that both sector universities had the required offices, staff members and managers. The areas where private universities were observed weak as compared to public universities were lack of proper staff vacancy advertisements and induction policies, vague appraisal system, low salary packages and limited freedom to managers. Public universities were found unsatisfactory in areas including staff induction on merit based policies and political intervention, lack of monitoring system and lack of collegiality amongst university offices. The study recommends that universities in both sectors should prepare staff and student manuals for transparency procedures, should improve the skills and knowledge of its staff/managers by conducting seminars/ workshops/ trainings in collaboration with HEC and other regulatory bodies on regular basis, and establish public private partnership to improve university management system in Pakistan.